Inventing and validation of questionnaires Muslim doctor questionnaire (MDQ) & Muslim medical student questionnaire (MMSQ) - Musa, Ramli; Abdul Rani, Mohammad Fauzi; Che Ahmad, Aminudin (2014)
Background: